Discharge-ready volume status in acute decompensated heart failure: a survey of hospitalists - Anna M. Maw; Brian P. Lucas; Brenda E. Sirovich; Nilam J. Soni (Greater Baltimore Medical Center, 2020)
Acute decompensated heart failure is the leading cause of hospitalization in older adults. Clinical practice guidelines recommend patients should be euvolemic at hospital discharge - yet accurate assessment of volume status is recognized to be exceptionally challenging. This conundrum led us to investigate how hospitalists are assessing volume status and discharge- readiness of patients hospitalized with heart failure. We collected audience response data during a didactic heart failure presentation at the 2019 Society of Hospital Medicine annual meeting. Respondents (n = 216), 76% of whom were practicing physician hospitalists caring for more than 20 acute heart failure patients per year, were presented six questions. Eighteen percent of respondents reported not being able to determine the completeness of decongestion on discharge and 32% reported that complete decongestion was not a treatment target. These findings suggest important differences between guideline recommendations and how hospitalists treat heart failure in current clinical practice.